A REFERENCIAÇÃO NA CONSTRUÇÃO DA IDENTIDADE E DA REPRESENTAÇÃO FEMININA NO ANÚNCIO PUBLICITÁRIO BRASILEIRO. - ARAUJO, Keila de Jesus Ribeiro (2019)
It is proposed in this dissertation an articulation between the notion of Cultural Identity outlined by Hall (2006) and Bauman (2005), the concept of Social Representation elaborated by Moscovic (2007) and the of the Referent or object of the speech constructed by Mondada and Dubois (1996), through stereotypes from the perspective of Amossy and Pierrot (2010). Identity in postmodernity is neither stable nor predetermined, but rather has a fluid character. In other words, it is (re) modeled according to the positions that subjects assume within certain social, cultural and historical contexts. One of the responsible factors for these displacements is Globalization, a phenomenon that constantly transforms the global environment in space and time. Thus, there is no single identity but identifications that are used by the subjects according to the social positions they occupy at certain moments. Identifications arise from the stereotypes, a type of reference representation crystallized in the collective memory of different social groups, but that can undergo changes from the representations of use, giving rise to new identifications. At the same time as it manufactures identifications, the different stereotypes also produce new referents / objects of discourse that can be materialized in diverse and varied texts, particularly in advertisements, which are ubiquitously present in society’s daily life, undergoing constant changes to better address its target audience. The referent / object of speech is an abstract entity produced at the moment of interaction from the social context and cognitive operations, according to reality and through negotiation. In addition to reconstructing the referent, the phenomenon of referencing through referential processes (referential introduction, anaphora, deixis) can also (re) construct social identifications and representations. In this research we aim to analyze how the referential processes contribute to the construction of the female identity, representation and referral from stereotypes found in advertisements for makeup, beer, and cleaning material. The analysis of the data is qualitative and has explanatory character, as we investigate how these phenomena occur in situations of use that are established by the stereotypes around women in advertisements. Through this analysis we see that referential processes are indispensable resources in the reconstruction of identifications / representations / referents because they have, in their constitution, the recategorizing character, thus attending to the mobile capacity of cultural identifications, of social representations, and of the objects of discourse (referents).